2020
DOI: 10.1111/jch.14105
|View full text |Cite
|
Sign up to set email alerts
|

Isolated systolic hypertension and central blood pressure: Implications from the national nutrition and health survey in Taiwan

Abstract: Isolated systolic hypertension (ISH) is defined as systolic blood pressure (SBP) ≥140 mmHg and diastolic blood pressure (DBP)<90 mmHg. 1 The prevalence of ISH increases with age along with the decreasing DBP and the widening pulse pressure (PP). ISH is commonly viewed as the manifestation of vascular aging and is conceivably the most common subtype of hypertension in the elderly population. 2-4 The elderly with ISH have a significantly higher risk of cardiovascular diseases 5,6 and benefit substantially from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, in recent decades the ISH prevalence has also increased in young adults due to the epidemic of overweight and obesity [ 10 , 11 ]. The prevalence of ISH has been reported different from 6.51 to 35%, which depend on the definition of ISH and distribution of age, sex, race and other variables in the studied populations [ 9 , 12 – 15 ]. It has shown that systolic blood pressure plays a greater role in cardiovascular disease than diastolic blood pressure [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent decades the ISH prevalence has also increased in young adults due to the epidemic of overweight and obesity [ 10 , 11 ]. The prevalence of ISH has been reported different from 6.51 to 35%, which depend on the definition of ISH and distribution of age, sex, race and other variables in the studied populations [ 9 , 12 – 15 ]. It has shown that systolic blood pressure plays a greater role in cardiovascular disease than diastolic blood pressure [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…When using brachial BP only for the evaluation of therapeutic effi cacy of current patient antihypertensive medication, we may omit the central systolic hypertension, which has deleterious effect on heart, brain, kidneys and arteries. Brachial blood pressure may overestimate the control of hypertension (25,26). Patients may suffer from unrecognized hypertension with all negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Prevailing central systolic or brachial systolic BP in individual patient can be expressed also by cSBP/brachSBP ratio; the value above 1.0 expresses a higher central systolic BP; value below 1.0 expresses a higher brachSBP. The prevalence of central systolic hypertension is very frequent in isolated systolic hypertension (ISH) and is frequently associated with a central obesity (26).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from Taiwan among drug naïve adults ≥19 years, the prevalence rates of ISH and IDH were 6.51% and 1.92%, respectively. [ 6 ] According to the National Health and Nutrition Examination Survey (1999–2010), the prevalence of untreated ISH was 9.3% in the United States of America. [ 7 ] Most studies in India have been restricted to the district population, and the prevalence estimates for ISH vary between 4.3%[ 8 ] to 13.3%.…”
Section: Introductionmentioning
confidence: 99%